A Application of Six Sigma and FMEA Methods for Defect Reduction in Woven Bag Production - Faris Yasin Rochmatullah; Rusindiyanto Rusindiyanto (ITEJ (Information Technology Engineering Journals), 2025)
This study aims to reduce the number of defects in the production of woven bags, which experiences product defects ranging from 4.1% to 5.4%. The method used is Six Sigma with the DMAIC (Define, Measure, Analyze, Improve, Control) approach to improve product quality. Root cause analysis was carried out using fishbone diagrams and Failure Mode and Effect Analysis (FMEA) which identified four main factors causing defects, namely humans, machines, materials, and methods. The results showed that the defects that had the most effect on the production process were perforated weaving, stretched weaving, and miss print. From the data analyzed for the period January to December 2024, a Defects Per Million Opportunities (DPMO) value of 6,746,655 and a sigma level of 3.97 were obtained, which shows that even though the production process is good enough, there is still room for improvement. Improvement recommendations include increased quality supervision and regular calibration of machines to achieve better quality targets. With the application of the Six Sigma method, it is hoped that the company can achieve a significant reduction in the defect rate and improve overall production performance.